2005
DOI: 10.1242/dev.02098
|View full text |Cite
|
Sign up to set email alerts
|

Homeotic factor ATBF1 induces the cell cycle arrest associated with neuronal differentiation

Abstract: The present study aimed to elucidate the function of AT motif-binding factor 1 (ATBF1) during neurogenesis in the developing brain and in primary cultures of neuroepithelial cells and cell lines (Neuro 2A and P19 cells). Here, we show that ATBF1 is expressed in the differentiating field in association with the neuronal differentiation markers β-tubulin and MAP2 in the day E14.5 embryo rat brain, suggesting that it promotes neuronal differentiation. In support of this, we show that ATBF1 suppresses nestin expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 35 publications
4
83
1
Order By: Relevance
“…40,41 Association with CRM1, an exportin, might be another important molecular mechanism that regulates the nucleus-cytoplasm transfer of ATBF1. 20 In conclusion, we have revealed that ATBF1 in the nucleus negatively regulates the MUC5AC gene in gastric cancer by binding to an AT motif-like element in the MUC5AC promoter.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…40,41 Association with CRM1, an exportin, might be another important molecular mechanism that regulates the nucleus-cytoplasm transfer of ATBF1. 20 In conclusion, we have revealed that ATBF1 in the nucleus negatively regulates the MUC5AC gene in gastric cancer by binding to an AT motif-like element in the MUC5AC promoter.…”
Section: Discussionmentioning
confidence: 66%
“…19 Thus, not only the expression levels of ATBF1, but also its subcellular localization, appear to be linked to cell differentiation and induction of cell cycle arrest. 20 The present study of mucin expression in gastric cancer and the functions of ATBF1 [21][22][23] has revealed that the expression of ATBF1 in the nucleus suppresses MUC5AC expression in gastric cancer. This is the first report to document the molecular mechanism of altered expression of MUC5AC, as regulated by ATBF1, in gastric cancer.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Atbf1 has been reported to exert roles in control of cell proliferation (24). Although Atbf1 gene-trap mutants failed to display overt defect in cell proliferation in early pituitary development, it remains possible that a trace amount of wt Atbf1 protein may adequately function to regulate subsets of its targets, whereas Pit1 ⌭⌭␣ would be particularly sensitive to Atbf1 levels.…”
Section: Differentiation Defects In Pit1 Lineage In Atbf1 Gene-trap Mmentioning
confidence: 99%
“…Xu et al: Evaluation of novel SNPs and haplotypes within the ATBF1 gene mor suppressor in several cancers (Kawaguchi et al, 2016;Sun et al, 2014Sun et al, , 2015. More importantly, it plays an important role in regulating myogenesis, adipose tissue development and transactivating the cell cycle inhibitor (Jung et al, 2005;Dean, 1997, 1999;Richard and Stephens, 2014).…”
mentioning
confidence: 99%